Targeting SPINK1 in the damaged tumour microenvironment alleviates therapeutic resistance. Issue 1 (December 2018) - Chen, Fei; Long, Qilai; Fu, Da; Zhu, Dexiang; Ji, Yan; Han, Liu; Zhang, Boyi; Xu, Qixia; Liu, Bingjie; Li, Yan; Wu, Shanshan; Yang, Chen; et al.
Abstract Chemotherapy and radiation not only trigger cancer cell apoptosis but also damage stromal cells in the tumour microenvironment (TME), inducing a senescence-associated secretory phenotype (SASP) characterized by chronic secretion of diverse soluble factors. Here we report serine protease inhibitor Kazal type I (SPINK1), a SASP factor produced in human stromal cells after genotoxic treatment. DNA damage causes SPINK1 expression by engaging NF-κB and C/EBP, while paracrine SPINK1 promotes cancer cell aggressiveness particularly chemoresistance. Strikingly, SPINK1 reprograms the expression profile of cancer cells, causing prominent epithelial-endothelial transition (EET), a phenotypic switch mediated by EGFR signaling but hitherto rarely reported for a SASP factor. In vivo, SPINK1 is expressed in the stroma of solid tumours and is routinely detectable in peripheral blood of cancer patients after chemotherapy. Our study substantiates SPINK1 as both a targetable SASP factor and a novel noninvasive biomarker of therapeutically damaged TME for disease control and clinical surveillance. Tumour microenvironment actively contributes to drug resistance in clinical oncology. Here, the authors show that genotoxic stress induces senescence in human stromal cells, which in turn secrete serine protease inhibitor Kazal type 1 (SPINK1) and promote acquired resistance of cancer cells via EGFR-mediated paracrine signaling.